Making Schools Resilient at Scale : The Case of Japan - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2017)
Japan's Program for Earthquake-Resistant School Buildings has increased the seismic safety of Japanese schools, and hence increased the safety of Japanese schoolchildren, teachers, and communities. Since 2003, when the program accelerated, the share of earthquake-resistant public elementary and junior high schools has increased, from under half of schools in 2002 to over 95 percent in April 2015. Japan is sharing knowledge from this program with developing countries through its relationship with the Global Facility for Disaster Reduction and Recovery (GFDRR), whose Global Program for Safer Schools has been supported by the Japan–World Bank Program for Mainstreaming Disaster Risk Management in Developing Countries and its implementing arm, the Disaster Risk Management Hub, Tokyo.